Implementasi Cyber Public Relations PT. Perusahaan Listrik Negara (Persero) Sumbawa Dalam Meningkatkan Citra Positif - Andy Eko Saputra (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Public Relations in enhancing the positive image of PT. Perusahaan Listrik Negara (PLN) Sumbawa. This study contributes to the understanding of the importance of Cyber PR in building a positive corporate image and provides recommendations for PT. PLN Sumbawa to further enhance Cyber PR practices. The research methodology used in this study is qualitative, with interviews as the data collection tool. The study reveals that PT. PLN Sumbawa understands the importance of Cyber PR in maintaining and improving the company's image. The company utilizes various types of Cyber PR media, including online media, online mass media, and social media. The services provided in Cyber PR media include wire service. Furthermore, PT. PLN Sumbawa is actively engaged in various Cyber PR activities such as advertising, lobbying, press activities, promotions, and publicity. The company utilizes online media and social media to convey information, provide services, and carry out campaigns to strengthen the positive image. Evaluation of Cyber PR activities is conducted by measuring the effectiveness of content based on the number of likes, shares, and responses from the public. In the formation of the company's positive image, PT. PLN Sumbawa successfully fulfills the cognitive, attitudinal, perceptual, and motivational.